Implementation obstacles and strategy implementation failure - Candido, Carlos (2019)
Purpose – The paper addresses the following question: How do strategy implementation obstacles relate to each other and affect strategy implementation? Method – The research methodology is qualitative and based on an extensive review of the literature and on an in-depth case study analysis. Findings – This paper draws two main conclusions. The first is that the many obstacles that impact the strategy implementation process can interact and be strongly interrelated in dynamic and complex manners. The second is that obstacles can lead to and reinforce other obstacles, eventually forming long chains of blockages. Originality – Strategy implementation remains a difficult task with improbable success. This paper provides a contribution to an explanation on why so many strategy implementation efforts fail. It is one of the very few papers addressing the issue of the relationships between strategy implementation obstacles.